2015
DOI: 10.12988/ams.2015.54300
|View full text |Cite
|
Sign up to set email alerts
|

Clique domination in a graph

Abstract: Let G be a nontrivial connected graph. A nonempty subset S of V (G) is a clique dominating set of G if S is a dominating set and the induced subgraph S of S is complete. The minimum cardinality among all clique dominating sets of G, denoted by γ cl (G), is called the clique domination number of G. A clique dominating set S of G with |S| = γ cl (G) is called a γ cl-set of G. This study aims to characterize the clique dominating sets in the join, corona, composition and cartesian product of graphs and determine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 3 publications
0
8
0
Order By: Relevance
“…where S ⊆ V (G) and T x ⊆ V (H) for each x ∈ S. Specifically, T x = {a ∈ V (H) : (x, a) ∈ C} for each x ∈ S. Some parameters studied on these types of graphs can be found in [6] and [7].…”
Section: Terminology and Notationmentioning
confidence: 99%
“…where S ⊆ V (G) and T x ⊆ V (H) for each x ∈ S. Specifically, T x = {a ∈ V (H) : (x, a) ∈ C} for each x ∈ S. Some parameters studied on these types of graphs can be found in [6] and [7].…”
Section: Terminology and Notationmentioning
confidence: 99%
“…So far, there is a significant number of variants of hop domination that have been defined and investigated. Some studies on hop domination, its variants, and related concepts can be found in [1], [2], [5], [8], [7], [9], [13], [14], [15], [19], [20], and [21].…”
Section: Introductionmentioning
confidence: 99%
“…Domination and some variations of the concept are found in the book by Haynes et al (see [9]). Other variations of domination can be found in [2], [3], [4], [5], [11], [12], [16], and [18]. The concepts of locating, stricly locating, locating-dominating, and strictly locating-dominating, and the associated parameters are studied in [6], [8], [10], [13], [14], [15], [17], [19], [20].…”
Section: Introductionmentioning
confidence: 99%